BRAF mutations in sporadic colorectal carcinoma from polish patients - Wójcik, Piotr; Okoń, Krzysztof; Osuch, Czesław; Klimkowska, Agnieszka; Tomaszewska, Romana (Polish Journal of Pathology, 2010)
BRAF mutations are second to KRAS mutations in activation of the MAPK pathway in colorectal carcinoma cells. In addition to mutated KRAS, BRAF V600E mutation is associated with resistance to EGFR-targeted therapy in colorectal cancer; thus mutated BRAF might serve as a predictive factor. In this study, 163 routinely resected adenocarcinomas were screened for mutations in exons 11 and 15 of the BRAF gene. Only 6 (3.7%) tumours had a missense point mutation (G469A, D594G, G596R, K601N and twice V600E). The tumours were locally advanced with multiple metastases to lymph nodes. Mutations were associated with microsatellite instability (2 cases MSI-H, 2 cases MSI-L) and mutually exclusive with a mutated KRAS gene. In this sample set, mutations in the BRAF gene were more diverse and less frequent than usually reported.